Piero Pincharo de Parma, un ragioniere italiano in suolo ungherese - Kuffart, Hajnalka (Verbum – Analecta Neolatina, 2012)
During the time of Ippolito d'Este's archbishopric in Esztergom, Hungary, an Italian officer was leading the economic accounting, whose name was Piero Pincharo de Parma. His books are considered to be essential sources for researchers of the Hungarian Middle Ages. Investigating his character, we can get closer to the order of the accountancy, his responsibilities, and we can follow his life in Hungary.